Newborn care practices in urban slums of Lucknow city, UP - Gupta Pratibha; Srivastava V; Kumar Vishwajeet; Jain Savita; Masood Jamal; Ahmad Naim; Srivastava J (Wolters Kluwer Medknow Publications, 2010)
Objectives: To study the knowledge and practices related to newborn care in urban slums of Lucknow city, UP, and to identify critical behaviors, practices, and barriers that influence the survival of newborns. Materials and Methods: A cross-sectional study in urban slums of Lucknow city, UP, included 524 women who had a live birth during last 1 year preceding data collection. Data were analyzed using statistical software SPSS 10.0 for windows. Results: Study findings showed that about half of the deliveries took place at home. Majority (77.1%) of the mothers believed that baby should be bathed with warm water and dried with clean cloth and 79.7% mothers practiced it. Only 36.6% mothers initiated breast-feeding within 1 h of birth and 30.2% initiated after 1 day. The mothers who have not given colostrum to their baby, in majority the reason was customs. Conclusion: In majority of cases, correct knowledge and correct practices regarding newborn care were lacking among mothers and this should be promoted through improved coverage with existing health services.